(untitled) (Journal of Modern Mechanical Engineering and Technology, 2022)
Abstract: This inclusive study reports the effect of the Nd atoms on the mechanical, microstructural, electrical and superconducting characteristics of Y0.9Ho0.1Ba2-yNdyCu3O7-δ superconductors with the aid of standard characterization methods, including X-ray diffraction, scanning electron microscopy, the bulk density, dc resistivity, and transport critical current density. The experimental results such as the degree of granularity, hole localization effect, room temperature resistivity, critical transition temperature, degree of the broadening, thermodynamic fluctuations, crystallinity, crystal plane alignments, crystal structure, grain size, phase purity and lattice parameters, the appearance of flux pinning centers, grain boundary weak-links, surface morphologies elemental compositions and distributions belonging to Y-site Ho and Ba-site Nd substituted Y-123 superconducting samples are discussed in detail for the first time. All the experimental findings show that the microstructural, electrical, mechanical and superconducting properties regularly improve with the increment in the HcN (Ho constant+Nd changeble) until a certain value of y=0.100, beyond which the characteristics tend to retrograde rapidly. This is attributed to the fact that excess penetration of the Nd damages the crucial properties given above.